2000
DOI: 10.1007/s11661-000-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

Improved microstructure and properties of 6061 aluminum alloy weldments using a double-sided arc welding process

Abstract: Due to its popularity and high crack sensitivity, 6061 aluminum alloy was selected as a test material for the newly developed double-sided arc welding (DSAW) process. The microstructure, crack sensitivity, and porosity of DSAW weldments were studied systematically. The percentage of fine equiaxed grains in the fully penetrated welds is greatly increased. Residual stresses are reduced. Porosity in the welds is reduced and individual pores are smaller. It was also found that the shape and size of porosity is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…[27] Zhang et al [16] reduced the formation of columnar structures in Al 6061 weldments by double arc welding, and consequently, metallurgical properties of welds were improved. Yongyuth et al [28] and Qiu et al [29] found that the toughness of castings and welds could be improved by increasing the volume fraction of the equiaxed zone.…”
Section: Effects Of Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…[27] Zhang et al [16] reduced the formation of columnar structures in Al 6061 weldments by double arc welding, and consequently, metallurgical properties of welds were improved. Yongyuth et al [28] and Qiu et al [29] found that the toughness of castings and welds could be improved by increasing the volume fraction of the equiaxed zone.…”
Section: Effects Of Microstructurementioning
confidence: 99%
“…[16] Consequently, the width of CDZ would decrease with the increase in welding current. According to the theory of Hunt, fully equiaxed growth occurs when the following is true [32] :…”
Section: Effects Of Welding Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when applying conventional fusion welding techniques, butt joints or lap joints, typically encountered in the assembly of long and (or) large structural products, are especially challenging to manufacture without distortion and defects. Aluminium alloys of the 6000 series have high thermal conductivity, high strength, and low weldability; this combination of properties necessitates the use of special welding procedures to prevent solidification cracking and to minimize residual stresses (Indira Rani et al, 2011;Zhang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Double-sided arc welding (DSAW) is a new arc welding process invented and developed at the University of Kentucky [1][2][3]. The DSAW system uses two torches on the opposite sides of the workpiece to force the welding current to flow through the thickness of the workpiece disconnected from the power supply ( figure 1(b)).…”
Section: Introductionmentioning
confidence: 99%